Shellfish subsidies along the Pacific coast of North America. Issue 5 (27th January 2020) - Cox, Kieran D.; Davies, Hailey L.; Davidson, Katie H.; Gerwing, Travis G.; Dudas, Sarah E.; Juanes, Francis
Abstract : Spatial subsidies are associated with pronounced ecosystem responses, as nutrients cross ecological boundaries and cascade through food webs. While the importance of subsidies is known, the role of shellfish, specifically molluscs, as a marine subsidy has not been formally described. Focusing primarily on the Pacific coast of North America, we identify vectors that transport shellfish‐derived nutrients into coastal terrestrial environments, including birds, mammals, and over 13 000 yr of marine resource use by people. Evidence from recipient ecosystems suggests shellfish drastically influence soil chemistry, forest productivity and the diversity of primary producers at the regional and landscape level. Responses in higher trophic levels have not yet been investigated, but given documented responses in lower trophic levels, this may be due to a lack of examination. To determine if the processes we describe within the northeast Pacific are pertinent to coastal environments worldwide, we also explore shellfish subsidies globally, with a specific focus on temperate and tropical islands. As shellfish are not as spatially or temporally constrained as other subsidies, our examination suggests our findings are applicable to many other geographical regions along the marine–terrestrial interface.